California Dentists' Engagement in Media Advocacy for Sugar Restriction Policies. (April 2022) - Kearns, C.E.; Urata, J.; Chaffee, B.W.
Objectives: Increasing dentists' visibility in the media to make the case for sugary beverage taxes can help advance public policy that improves oral health outcomes. We assessed California dentists' media engagement behaviors related to sugar restriction policies for dental caries prevention and correlates of engaging in such behavior. Methods: Survey items related to sugar policies and media engagement were embedded in an electronically distributed statewide survey of dentists' tobacco cessation counseling behaviors. Descriptive statistics were calculated for respondent characteristics, perceived professional responsibility to discuss selected topics with patients, and attitudes and behaviors related to sugar restriction policy and media communication. Multivariable models identified independent correlates of media engagement. Results: Of 624 respondents, most had never talked to traditional media (78%) or posted to social media (64%) about sugar or sugar policies for dental caries prevention. Respondents with the highest level of media engagement were more likely to agree that sugary beverage taxes are effective at reducing dental caries, that they had support from dental professional organizations to talk to the media, that it is realistic for patients to reduce their sugar consumption, and that sugar and sugary drinks are extremely harmful to health. Conclusions: Efforts to increase dentists' media engagement related to sugar restriction policies for dental caries prevention should address dentists' negative attitudes toward the effectiveness of sugar restriction policies and may require increased support from dental professional societies. Knowledge Transfer Statement: Study findings identify dentists' low engagement in media advocacy to support sugar restriction policy adoption. The results identify correlates of media engagement and of dentists' willingness and confidence to act, which could serve to inform interventions to support and enhance engagement.